Evaluasi User Experience Sistem Informasi Akademik Mahasiswa pada Perguruan Tinggi Menggunakan User Experience Questionnaire - Silvana Rasio Henim; Rika Perdana Sari (Politeknik Caltex Riau, 2020)
User experience describes the experience gained by users when using software products. Focus on the needs and emotions of users when using a product is one of the keys to the success of a software. As a software product, Student Academic Information Systems have an important role to improve services to students in Higher Education. Measurement of user experience aims to determine the experience gained by users when using the Student Academic Information System. Measurements were made using the User Experience Questionnaire (UEQ) on 179 active student of a higher education institution in Pekanbaru. The results obtained for each aspect of UEQ are 1.395 attractiveness, 1.586 clarity, 1.380 efficiency, 1.392 accuracy, 1,347 stimulation and 0.847 novelty. The lowest value is in the novelty aspect. The novelty aspect needs to be a concern because users feel the monotonous and usual novelty so that it has a negative impression value. The results of this study can be used as recommendations for designing a new Student Academic Information System user experience.